Mixed cestode infection: an incidental association in an immunocompetent person. (10th December 2012) - Aggarwal, Puneet; Kumar, Gunjan; Dev, Nishanth; Jain, Shalabh
Abstract : Echinococcus and Taenia infection are the two most relevant forms of cestode infection in humans. These infections occur worldwide, but with higher prevalence in developing countries like India, where poor hygiene facilitates their transmission. We report a case of a middle-aged man who presented with seizures and was found to have dual worm infection including Taenia and Echinococcus. The patient was treated with steroids and albendazole followed by PAIR (puncture, aspiration, injection of scolicidal agent and reaspiration). After 6 months of follow-up, the patient is asymptomatic and seizure-free without any relapse.